2010
DOI: 10.1177/0969733010364893
|View full text |Cite
|
Sign up to set email alerts
|

Do-not-resuscitate orders for critically ill patients in intensive care

Abstract: End-of-life decision making frequently occurs in the intensive care unit (ICU). There is a lack of information on how a do-not-resuscitate (DNR) order affects treatments received by critically ill patients in ICUs. The objectives of this study were: (1) to compare the use of life support therapies between patients with a DNR order and those without; (2) to examine life support therapies prior to and after the issuance of a DNR order; and (3) to determine the clinical factors that influence the initiation of a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
32
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(35 citation statements)
references
References 20 publications
1
32
2
Order By: Relevance
“…Prior studies suggest that physicians do not readily refer and admit older individuals >80 years to ICU despite a clear indication of the need to do so, and those admitted to the ICU often receive lesser intensive treatment (IMV and renal support), compared to patients <80 years, even after adjusting for illness severity [17,18]. Also, old age being a significant factor influencing the issue of ‘Do not resuscitate or intubate’ order, may result in decreased intensive management, partly explaining for the reduced use of IMV in critically ill elderly patients [19,20]. …”
Section: Discussionmentioning
confidence: 99%
“…Prior studies suggest that physicians do not readily refer and admit older individuals >80 years to ICU despite a clear indication of the need to do so, and those admitted to the ICU often receive lesser intensive treatment (IMV and renal support), compared to patients <80 years, even after adjusting for illness severity [17,18]. Also, old age being a significant factor influencing the issue of ‘Do not resuscitate or intubate’ order, may result in decreased intensive management, partly explaining for the reduced use of IMV in critically ill elderly patients [19,20]. …”
Section: Discussionmentioning
confidence: 99%
“…83,93 Although patient autonomy played an important role, 72,75,89 particularly among nurses, 73 one study 64 found that it did not significantly change the physician's decision. However, the presence of family, particularly adult children as surrogate decision-makers, 72,84,85 often aided decision-making.…”
Section: Key Decision-makersmentioning
confidence: 99%
“…The timings were described as days to death or days from admission, so it was difficult to identify commonalities of the timings of decision-making. DNACPR order decision-making ranged from admission or within 24 hours of admission 15,74,75,84,88,94 to less than 7 days before death. 79,84,85 Sometimes there were less than 24 hours before death, 84,85 with many emergency teams having to decide moments before death whether or not there was a DNACPR order already in place.…”
Section: Timingmentioning
confidence: 99%
See 2 more Smart Citations